2022
DOI: 10.1088/1748-0221/17/07/t07001
|View full text |Cite
|
Sign up to set email alerts
|

Real-time tracking of source movement by Cherenkov emission imaging for high-dose-rate brachytherapy

Abstract: Quality assurance (QA) of the source movement is essential for ensuring the safe delivery of high-dose-rate (HDR) brachytherapy. Here, we proposed a simple and effective method for real-time tracking of the source movement in high-dose-rate brachytherapy based on Cherenkov emission imaging. The Cherenkov light emitted from water irradiated by 192Ir-source γ-rays was captured using a high-sensitivity video camera. The source positions and dwell intervals were determined from the light images and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Figure 1(a) presents a schematic of the setup (Yogo et al 2020a(Yogo et al , 2021(Yogo et al , 2022. Pure water (Elix Advantage, Merck KGaA; Darmstadt, Germany) was used to eliminate contamination.…”
Section: Imaging Systemmentioning
confidence: 99%
“…Figure 1(a) presents a schematic of the setup (Yogo et al 2020a(Yogo et al , 2021(Yogo et al , 2022. Pure water (Elix Advantage, Merck KGaA; Darmstadt, Germany) was used to eliminate contamination.…”
Section: Imaging Systemmentioning
confidence: 99%
“…Other potential uses of the REA localization capability is in Radioisotope Identification (RIID) in health safety and national security [6]. Various detectors have been used in radioactive source localization [7][8][9][10][11][12][13][14]: radiosensitive films, at panel detectors (Electronic Portal Imaging Device (EPID)), gamma camera, photon counting detectors, scintillators, and others. Typically the detector is at a fixed position and radioactive sources are either static or moving.…”
Section: Introductionmentioning
confidence: 99%
“…Several research studies have shown promising results and potential clinical impact for use of in-vivo source tracking for prostate [ 9 , 10 , 11 , 12 , 13 , 14 ], gyno [ 15 ] and general HDR applications [ 16 , 17 , 18 , 19 ]. Some of these studies have adopted silicon diodes, in the form of single devices, linear or 2D arrays showing positive results in source tracking [ 15 , 20 ].…”
Section: Introductionmentioning
confidence: 99%